Effects Of Early Trauma and Recent Stressors on Depression, Anxiety, and Anger - Seok, Bum Joon; Jeon, Sehyun; Lee, Jooyoung; Cho, Seong-Jin; Lee, Yu Jin; Kim, Seog Ju (Frontiers in Psychiatry, 2020)
Background Early life traumatic events and recent stressful events are known to have especially strong effects on emotional wellbeing. However, little is known about the interaction of early and recent stressors on emotions. We aimed to examine the interactive effects of early trauma and recent stressors on depression, anxiety, and anger. Methods One hundred and seventy adults were recruited and asked to complete the Center for Epidemiological Studies Depression Scale (CES-D), the state anxiety subscale of the State–Trait Anxiety Inventory (STAI-S), and the state anger subscale of the State–Trait Anger Expression Inventory (STAXI-S). Early traumas and recent stressors were assessed during face-to-face interviews. Multiple regression analysis was performed to test whether early trauma, recent stressors, and the interaction of the two would predict CES-D, STAI-S, and STAXI-S scores. Results In the multiple regression models, STAI-S scores were predicted only by recent stressors (R2 = 0.063, p = 0.001). In contrast, CES-D and STAXI-S scores were predicted only by the synergistic interaction of early trauma with recent stressors (R2 = 0.075, p < 0.001; R2 = 0.039, p = 0.01, respectively). Conclusions A synergistic interaction effect between early trauma and recent stressful events on current depression and anger was observed, indicating that the combined effects of early trauma and recent stressors are stronger than their individual effects. In contrast, anxiety was affected mainly by recent stressors. Our findings suggest that the form that emotional disturbance takes can vary depending on the timing of stressors.